Improved Bioavailability and Bioaccessibility of Lutein and Isoflavones in Cultured Cells In Vitro through Interaction with Ginger, Curcuma and Black Pepper Extracts - Bernhard Blank-Landeshammer; Gerald Klanert; Lisa Mitter; Sophia Turisser; Nicolas Nusser; Alice König; Marcus Iken; Julian Weghuber (Antioxidants, 2022)
Intestinal absorption is intrinsically low for lipophilic micronutrients and phytochemicals. Plant extracts acting as bioavailability enhancers can complement for this deficiency by modulation of both, physicochemical and biochemical parameters, in the absorption process. However, these interactions often are limited to specific conditions and the mechanisms and potential synergisms are poorly understood. In this work, we used a human intestinal cell line to characterize the impact of extracts from C. longa (curcuma), Z. officinale (ginger) and P.nigrum (black pepper) on uptake and transport rates of the xanthophylls lutein and zeaxanthin as well as soy isoflavones measured by HPLC-DAD. We found a significant increase in the uptake of lutein in the presence of curcuma extract and enhanced isoflavone transport rates mediated by curcuma and ginger extracts. Combinations of the plant extracts did not lead to any additional increase in uptake or transport rates. By investigation of mixed micelle incorporation efficiency, we could dismiss changes in bioaccessibility as a potential enhancing mechanism in our experimental setup. We further conducted a rhodamine 123 efflux assay and discovered inhibition of P-glycoproteins by the ginger and black pepper extracts, highlighting a plausible route of action leading to increased isoflavone bioavailability.